REPRESENTASI PESAN DAKWAH DALAM PERSPEKTIF KOMUNIKASI ISLAM PADA FILM “BILA ESOK IBU TIADA” MENURUT CLIFFORT GEERTZ DAN GEORGE HERBERT (TEORI INTERAKSIONISME SIMBOLIK) - Usman Usman; Firdaus El Hadi; Sartika Sartika (Ensiklopedia of Journal, 2026)
Films are very popular among the public today, the function of films as entertainment but without realizing it has a meaningful message contained in the content of the film's story. This study examines the film "Bila Esok Ibu Tiada" which has a cultural semiotic meaning and symbolic interactionism that occurs in the relationship between mother and child and all family members. This study aims to interpret the meaning contained in the film from the semiotic and interaction side as well as the religious teachings implied in each scene obtained. This research method is a qualitative descriptive study with a literature approach. From the results of observations, there are 8 scenes that are very prominent to study the semiotic meaning. This study uses two studies, namely semiotics according to Clifford Geertz and Gorge Herbert, known as the theory of symbolic interactionism. The discussion in this study is seen from the scene and the meaning of each scene or dialogue and the atmosphere in the story.Keywords: Message, Perspective, Film